Pentingnya Dekriminalisasi Penyalah Guna Narkotika melalui Asesmen Terpadu dalam RUU Narkotika - Fadholi, Ahmat; Surtikanthi, Dian; Annisya, Sri (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
Prisoners in prison are dominated by narcotics cases, causing overcapacity. Responding to this problem, a decriminalization policy is needed for Narcotics abusers so that they can be placed in rehabilitation institutions. In decriminalization, Narcotics abuse is an unlawful act but the sanction given is in the form of rehabilitation. The TAT assessment, which is part of the decriminalization policy, aims to determine the role of a suspect in a narcotics crime, whether he is a drug abuser or a dealer and to determine his level of narcotics dependence. Thus the policy of decriminalization with rehabilitation punishment can be appropriately given to suspects who are addicted to Narcotics. However, the implementation of the TAT policy is still unknown whether it has been running effectively or not. The purpose of the article is to identify how the decriminalization of Narcotics through TAT has been implemented so far, by looking at the obstacles to implementation. The results of the study found that the obstacles in implementing the TAT were the unclear phrases in Article 111 and Article 112; there is no regulation regarding integrated assessment in Law no. 35 of 2009 concerning Narcotics; problems in the implementation of rehabilitation; less optimal implementation of integrated assessments and minimal awareness of facilities and infrastructure as well as human resources in implementing rehabilitation; and the lack of availability of facilities and infrastructure as well as human resources. Keywords: Decriminalization, Narcotics, Integrated Assessment Team